Efektivitas Hukum Dalam Pelaksanaan Sertifikasi Halal Oleh Pelaku Usaha Mikro, Kecil dan Menengah Di Kota Bandar Lampung - surya prameswari, regita; Sepriyadi Adhan; Harsa Wahyu Ramadhan; Ahmad Zazili; Nenny Dwi Ariani (Progressive Law Review, 2025)
Law Number 33 of 2014 concerning Halal Product Assurance requires halal certification for products circulating in Indonesia. However, in Bandar Lampung City, many micro and small business actors have not been halal certified. This study aims to analyze the implementation of halal certification by these business actors as well as its supporting and inhibiting factors. This type of research is an empirical normative law with a descriptive approach, using interviews, literature studies, and questionnaires for data collection. The results show that halal certification in Bandar Lampung City is not optimal, with the main obstacles in the form of lack of understanding, high costs, lack of socialization, and weak law enforcement. Instead, the success of certification is supported by clear regulations, awareness of the Islamic community, product testing laboratories, and a free consulting and certification program (SEHATI).